Effects of 8 weeks of moderate physical training on body composition, lipid profile, inflammatory markers, and physical activity in middle aged females - Sellami, Maha; Almuraikhy, Shamma; Anwardeen, Najeha; Nizamuddin, Parveen B.; Othman, Haitam; Alathba, Noora; Alareer, Noor; Elrayess, Mohamed A. (Frontiers in Endocrinology, 2026)
IntroductionModerate physical training is widely recommended for reducing cardiovascular risk in adults. However, its effects on body composition, lipid metabolism, inflammatory markers, and physical activity levels, along with the potential use of cytokines as biomarkers for evaluating training effectiveness, in middle-aged and older adults (30–60 years) remain to be investigated.MethodsParticipants aged 30–60 years underwent an 8-week of moderate-intensity aerobic training (MAT) program. Pre- and post-intervention assessments included body mass index (BMI); fat mass, muscle mass. Oxidative stress markers (superoxide dismutase [SOD] and catalase). Inflammatory cytokines (IL-6, IL-8, IL-10, IL-22, TNF-α [Tumor Necrosis Factor-alpha], MCP-1[Monocyte Chemoattractant Protein-1], IL-1RA). Lipid profile [total cholesterol, LDL-C [Low-Density Lipoprotein Cholesterol], HDL-C [High-Density Lipoprotein Cholesterol]. Telomere length, metabolic equivalent of task [MET], and the duration of vigorous and moderate physical activity per week.ResultsAfter 8 weeks of training, significant reductions were observed in BMI, fat free mass, muscle mass, and inflammatory cytokines (IL-22 &TNF-α). Oxidative stress markers showed increase in SOD level. Lipid profile analysis revealed decreases in total cholesterol, LDL-C, and HDL-C. Notably, there were significant increases in MET and moderate physical activity per week, indicating improved physical activity levels.ConclusionsThe reduction in pro-inflammatory cytokines aligns with the established anti-inflammatory benefits of regular exercise, contributing to the lower risk of chronic disease. However, the simultaneous decrease in anti-inflammatory cytokines suggests a complex and potentially age-specific immune adaptation to moderate training. Further investigation is warranted to clarify the implications of these immune responses and to refine exercise recommendations for optimal metabolic and immune health in these middle-aged females.